Implementasi SCRUM pada Pengembangan Aplikasi Sistem ADI STETSA SMAN 4 Malang: Bidang Kesiswaan - Muhammad Rifai; Aji Wibawa; Ilham Zaeni; Dony Setiawan (Universitas Ngeri Malang, 2021)
The development of an information system for SHS 4 Malang, including the field of student, was made to facilitate the management of data relating to students, parents, teachers, and employees. Student rights and responsibilities, including extracurricular activities, reporting breaches, and compassion initiatives, are governed by studentship. Agile development is being done in this project using the SCRUM methodology. The advantages of SCRUM are that it can save cost, time, and can cope with change. Five research sprints covering the period of December 20, 2021, to December 30, 2022, were completed. In sprint three, the student field worked on. This study's output is an information system for SMAN 4 Malang's student affairs. The report, kindness project, and extracurricular activities are the three features. These features are at the request of the person in charge of the student affairs field. Pengembangan sistem informasi untuk SMAN 4 Malang, termasuk bidang kesiswaan, dibuat untuk memudahkan pengelolaan data yang berkaitan dengan siswa, orang tua, guru, dan karyawan. Kesiswaan mengatur hak dan kewajiban siswa, seperti kegiatan ekstrakurikuler, pelaporan pelanggaran, dan proyek kebaikan. Pengembangan ini menggunakan metode agile dengan kerangka kerja SCRUM. Kelebihan dari SCRUM yaitu dapat menghemat biaya, waktu, dan dapat mengatasi perubahan. Penelitian ini dilakukan dari tanggal 20 Desember 2021 sampai 30 Desember 2022, dengan total lima sprint. Bidang kesiswaan dikerjakan pada sprint tiga. Hasil dari penelitian ini adalah sistem informasi untuk bidang kesiswaan di SMAN 4 Malang. Terdapat 3 fitur yaitu laporkan, proyek kebaikan, dan kegiatan ekstrakurikuler. Fitur-fitur tersebut telah sesuai dengan permintaan penanggung jawab bidang kesiswaan.